X-ray magnetic circular dichroism in d and f ferromagnetic materials: recent theoretical progress. Part I - Antonov, V.N.; Shpar, A.P.; Yaresko, A.N. (Физика низких температур, 2008)
The current status of theoretical understanding of the x-ray magnetic circular dichroism (XMCD) of 3d compounds is reviewed. Energy band theory based upon the local spin-density approximation (LSDA) describes the XMCD spectra of transition metal compounds reasonably well. Examples which we examine in detail are XPt₃ compounds (with X = V, Cr, Mn, Fe, Co, and Ni) in the AuCu₃ structure, Heusler compounds Co₂MnGe, Co₂NbSn, and compounds with noncollinear magnetic structure IrMnAl and Mn₃ZnC. Recently achieved improvements for describing the electronic and magnetic structures of 3d compounds are discussed.